2023
DOI: 10.1093/nar/gkad873
|View full text |Cite
|
Sign up to set email alerts
|

BioKA: a curated and integrated biomarker knowledgebase for animals

Yibo Wang,
Yihao Lin,
Sicheng Wu
et al.

Abstract: Biomarkers play an important role in various area such as personalized medicine, drug development, clinical care, and molecule breeding. However, existing animals’ biomarker resources predominantly focus on human diseases, leaving a significant gap in non-human animal disease understanding and breeding research. To address this limitation, we present BioKA (Biomarker Knowledgebase for Animals, https://ngdc.cncb.ac.cn/bioka), a curated and integrated knowledgebase encompassing multiple animal species, diseases/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The current data-dependent analysis of the human protein–disease association indicated that most of the membrane proteins are associated with multiple types of cancers. To investigate the biomarker status of the REMEMProt protein data, a search against the biomarker database Biomarker Knowledgebase for Animals was carried out ( Wang et al, 2024 ). The data revealed the potential role of the membrane proteins in various disease conditions such as diagnostic, prognostic, predictive, and therapeutic factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current data-dependent analysis of the human protein–disease association indicated that most of the membrane proteins are associated with multiple types of cancers. To investigate the biomarker status of the REMEMProt protein data, a search against the biomarker database Biomarker Knowledgebase for Animals was carried out ( Wang et al, 2024 ). The data revealed the potential role of the membrane proteins in various disease conditions such as diagnostic, prognostic, predictive, and therapeutic factors.…”
Section: Resultsmentioning
confidence: 99%
“…The enlisted proteins from human, and mouse, can be distinctively subjected to disease ontology analysis to visualize their associated diseases. Similarly, the biomarker status of the proteins was fetched from the Biomarker Knowledgebase for Animals database ( Wang et al, 2024 ) Furthermore, the proteins were also enriched for the information on cellular markers using the CellMarker 2.0 database ( Zhang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%